Oblicz Wynik przedstaw w najprostszej postaci pamiętaj o kolejności wykonywania działańia. (4 5/12+1 11/12)-(5 3/12-2 7/12)=​

Odpowiedź :

Hej!

Oto Twoja odpowiedź:

[tex](4 \frac{5}{12} + 1 \frac{11}{12} ) - (5 \frac{3}{12} - 2 \frac{7}{12} ) = \\ 5 \frac{16}{12} - (4 \frac{15}{12} - 2 \frac{7}{12} ) = 5 \frac{16}{12} - 2 \frac{8}{12} = \\ 3 \frac{8}{12} = 3 \frac{4}{6} = 3 \frac{2}{3} [/tex]

Pozdrawiam™

Odpowiedź:

(4 5/12+1 11/12)-(5 3/12-2 7/12)=

5 16/12-(4 15/12-2 7/12)=

5 16/12-2 8/12=

3 8/12=3 2/3

Szczegółowe wyjaśnienie: